Settlement analysis of treated soft clay using LECA replacement through numerical modelling - Azhani, Zukri (Penerbit UMP, 2021)
Soil replacement technique is the simplest and oldest way in improving the soft soil under the shallow foundations. The process started by taking or removing the un-wanted problematic part of soils and replacing it with other efficient materials. Therefore, this study conducted to analyse on the soft soil replacement using Lightweight Expanded Clay Aggregate (LECA) as a filling material instead of common aggregate. LECA has been widely used in geotechnical application as the materials were successfully recognized in minimising the dead loads by more than half. The settlement magnitude of treated soft soil with LECA replacement was analysed through finite element method by using PLAXIS 2D commercial software. The prediction graph for various internal friction angle has been developed for settlement estimation The graph was then validated using developed Settlement Prediction Model, analytical equations, and numerical analysis. Another finding from this study is a decrease in the magnitude of the settlement as the internal friction angle of LECA increases.